The theory and its reflection Research about the theory of Architecture - Yacoob, asaad Yacoob; Abood, Aday abas (Iraqi Journal of Architecture and Planning, 2009)
The theoretical side is very important in Architecture because the Architecture in one of its announcements is just material acumilate which reflects a thoughtfut dimension to know more about effect and affect, we have to make clear the theoretical sides that reflects on and reflects from it according to that theoretical dimension which takes it effects and its role in defining more clear the image of Architecture in future. we have to explain exchanged effects and affects between the Architecture and the theoretical side in the frame of a complete dimensions for both ofthem the material and the theorical’ Taking cure with the period differs ingrates and at last the thoughts results from according to the angles of analyzing and measuring. Adding to that what results from it and the effect that wasleft on. All points on the importance and the effict of globalization depending on the size of effection and its type which is actually left because it is expected that it will have its active role in creating the image skekage ofthe future the research us the principles ofthe explanation of this theory and its reflections on the Architecture and this refers to the descriptions of the image of architecture in the future depending on its affects on it’ Sowe have to make clear the gateral sides first of all then to make clear its special dimensions which provide basic information that make clear the type of data or its capacity ofbeing crystalanditreflectsontheArchitecture,lightenedwiththedesignedpoleprocessand describing its effects on architecture and what crystallize the image of response direction for this theory.